Quixalin in the treatment of dysenteriform diarrhea - Aswitha Damayanti; Sri S. Nasar; S. H. Pudjiadi (Paediatrica Indonesiana, 1973)
Quixalin is halquinol, a chlorinated hydroxyquinoline derivative developedin the Squibb Medical Research Laboratories.It is a chemically standardised mixture of controlled and reproduciblecomposition containing three chlorinated quinolines which are kept at a constant ratio.